Exploring goals and motivations of Māori heritage language learners - Te Huia, Awanui (Studies in Second Language Learning and Teaching, 2015)
Motivations of Māori heritage language learners are explored within this qualitative study. Te reo Māori (the Māori language) is currently classed as endangered (Reedy et al., 2011), which calls for the exploration of the motivational experiences of Māori heritage language learners. A total of 19 interviews with beginner, intermediate and advanced level learners were conducted. Results demonstrated how Māori heritage learners were motivated to learn due to their cultural heritage connection to the language and to other ingroup members. This study explores some of the motivations why Māori heritage language learners learn te reo Māori. For this group of indigenous language learners, cultural and language revitalisation are tied to language motivation. Furthermore, the ability to participate in cultural practices was central to language motivations.